PASEBAN KAWIS: PEMBERDAYAAN UMKM DESA KALIBARU MANIS BERBASIS TEKNOLOGI DIGITAL - auliya, yudha alif; Nurul Hadits; Muhammad Rafi Kurniawan; Abdurrahman Qoim Haqqi Muhammad (Dedication : Jurnal Pengabdian Masyarakat, 2025)
MSMEs play a major role in Indonesia’s economy, yet rural entrepreneurs still face challenges in digital literacy, branding, and modern marketing. Kalibaru Manis Village, with its potential in coffee, Etawa goat milk, and cassava chips (opak), struggles with product standardization, limited promotion, and low technology adoption. The PASEBAN KAWIS program was implemented using a Participatory Action Research approach through training, mentoring, and the use of an interactive digital module application. Evaluation with pre-test and post-test showed a significant increase in participants’ digital competence, from an average score of 51.1 to 83.5 or a 62.5% improvement, with 95% participation. Skills improved in product photography, branding, digital marketing, and marketplace utilization. In total, 93% of \participants found the program relevant to their business, and 87% were ready to apply digital strategies sustainably. By integrating technology and local wisdom, this program successfully enhanced MSME capacity and strengthened a village-based creative entrepreneurship ecosystem.